Optimal Placement and Sizing of Fault Current Limiters in Distributed Generation Systems Using a Hybrid Genetic Algorithm - Bayati, N.; Sadeghi, S. H. H.; Hosseini, A. (Engineering, Technology & Applied Science Research, 2017)
Distributed Generation (DG) connection in a power system tends to increase the short circuit level in the entire system which, in turn, could eliminate the protection coordination between the existing relays. Fault Current Limiters (FCLs) are often used to reduce the short-circuit level of the network to a desirable level, provided that they are dully placed and appropriately sized. In this paper, a method is proposed for optimal placement of FCLs and optimal determination of their impedance values by which the relay operation time, the number and size of the FCL are minimized while maintaining the relay coordination before and after DG connection. The proposed method adopts the removal of low-impact FCLs and uses a hybrid Genetic Algorithm (GA) optimization scheme to determine the optimal placement of FCLs and the values of their impedances. The suitability of the proposed method is demonstrated by examining the results of relay coordination in a typical DG network before and after DG connection.